2022
DOI: 10.3390/ijerph192315913
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Gut Microbiota Composition in Type 2 Diabetes Patients: A Population-Based Study

Abstract: (1) Background: A clinical laboratory index to assess gut dysbiosis is the F/B ratio < 0.8. In fact, an elevated proportion of Firmicutes and a reduced population of Bacteroides in diabetes type 2 (T2D) subjects has been observed. This study aimed to detail the dysbiosis status in the Italian population, focusing on some pathogenic spectra (T2D) or metabolic disorders. (2) Material and methods: A quantity of 334 fecal samples was analyzed in order to perform genetic testing and sequencing. (3) Results: A tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
0
11
2
Order By: Relevance
“…Although we did not observe changes in the F/B ratio between patients taking and not taking metformin, several studies have reported that obese and diabetic patients exhibit a higher F/B ratio compared to healthy subjects [ 30 , 31 ]. Patients taking metformin showed higher indices of alpha diversity, aligning with findings from previous studies [ 32 ].…”
Section: Discussioncontrasting
confidence: 93%
“…Although we did not observe changes in the F/B ratio between patients taking and not taking metformin, several studies have reported that obese and diabetic patients exhibit a higher F/B ratio compared to healthy subjects [ 30 , 31 ]. Patients taking metformin showed higher indices of alpha diversity, aligning with findings from previous studies [ 32 ].…”
Section: Discussioncontrasting
confidence: 93%
“…While the spread of antimicrobial-resistant bacteria in nosocomial facilities can be easily understood and, even if difficult to prevent, can be somehow contrasted, it is urgent to understand the increasing antibiotic resistance in the community, in agreement with other studies that confirmed the presence of CPO, MRSA, and VRE producers in the environment, where they can act as a reservoir of such resistance, their presence is nonetheless disturbing, as these genes can be transferred into human [ 34 ]. Moreover, many clinical and epidemiological studies indicate that antibiotic overuse can imbalance the composition of the gut microbiota, resulting in the emergence of antibiotic-resistant bacteria and the proliferation of opportunistic pathogens [ 35 , 36 ]. The presence of antibiotic residues in the environment can lead to contamination [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of cultivar., peanut-fed animals were characterized by a greater F/B ratio, which was driven by concurrent increases and decreases in Firmicutes and Bacteroidetes abundance, respectively. Increased F/B ratio has long been employed as a characteristic of the dysbiosis associated with obesity and T2D, with the surmise that the former is a consequence of higher caloric availability that may accompany this altered proportion ( 38 ). Despite the popularity of this measure, evidence from human and animal models has cast doubt on its usage and forenamed interpretation ( 14 , 39 , 40 ).…”
Section: Discussionmentioning
confidence: 99%